PENGARUH KOMPETENSI APARATUR,PARTISIPASI MASYARAKAT, DAN PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Kasus Pada Kecamatan Waru, Kabupaten Sidoarjo) - Apriliani, Nur Syndah; Yuliati, Anik (Journal of Information System, Applied, Management, Accounting and Research, 2024)
The aim of this research is to test, prove and analyze the influence of apparatus competency, community participation and internal control on accountability in village fund management. This research uses primary data in the form of distributed questionnaire data. The sample used was 100 respondents in Waru District, random sampling method. The analysis used in this research is partial least squares. Based on the research results, it can be concluded that the apparatus competency variable has no effect on the accountability of village fund management and the community participation variable. Meanwhile, the internal control variable influences the accountability of village fund management. The implications and suggestions are that strong internal controls can help prevent potential fraud and misuse of funds. This can create an environment free from unethical and harmful practices. With increased accountability, active community participation, and transparent use of funds, it is hoped that community trust in local government and the village fund management process will increase.